2018
DOI: 10.1177/0003489418771988
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Patients With Benign Paroxysmal Positional Vertigo and Severe Immobility Using the Particle Repositioning Chair: A Retrospective Cohort Study

Abstract: Objective: To report treatment of benign paroxysmal positional vertigo (BPPV) in patients unable to undergo traditional canalith repositioning maneuvers (CRMs) using a particle repositioning chair (PRC). Methods: A retrospective chart review was conducted at a single high-volume otology practice of patients diagnosed with BPPV from 2007 to 2017 with immobility prohibiting use of traditional CRMs. Patients were diagnosed and treated using a PRC, and outcome measures including resolution, recurrence, and number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Theoretically, this may improve treatment efficacy by loosening and acceleration of the otoconial debris within the SCCs (6,14,15). Furthermore, repositioning chairs allow treatment of immobile patients, who cannot undergo standard treatments with manual canalith repositioning maneuvers (19). Data from our clinic has showed that the TRV-chair is very efficient in the treatment of intractable BPPV cases (18).…”
mentioning
confidence: 97%
“…Theoretically, this may improve treatment efficacy by loosening and acceleration of the otoconial debris within the SCCs (6,14,15). Furthermore, repositioning chairs allow treatment of immobile patients, who cannot undergo standard treatments with manual canalith repositioning maneuvers (19). Data from our clinic has showed that the TRV-chair is very efficient in the treatment of intractable BPPV cases (18).…”
mentioning
confidence: 97%
“…One of the aims of this review was also to examine the indications for treatment in a repositioning chair, as very different indications for chair treatment currently exist. 14 It seems that the indications for repositioning chairs varied in the included studies. Specifically, 2 studies reported indication of treatment due to inability of successful manual CRP with cervical or lumbar spine disease.…”
Section: Discussionmentioning
confidence: 99%
“…For 1 of the studies, this can be explained by low sample size ( n = 34) or a high number of cases of non p -BPPV (38.2%) and multi-canal involvement (14.7%). 14 Another study had a non p -BPPV group of 19%, and 7% of subjects also suffered from Meniere’s disease, which could have contributed to the low success rate. 15 A lower rate of symptom relief was found in the group of patients with multi-canal affection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of the repositioning chairs over classical maneuvers include analytical feasibility and the treatment of people with low back and neck problems that make them unsuitable for manual treatments. Also, they have potential utility for complicated BPPV cases [Luryi et al, 2018;West et al, 2019;Abdulovski and Klokker, 2021]. Therefore, the aim of the present study was to analyze the outcomes of treatment of MC-BPPV with the TRV Chair and compare those results with manual maneuvers.…”
Section: Introductionmentioning
confidence: 99%